A STATISTICAL OVERVIEW ON THE PRODUCTS CERTIFIED WITH NATIONAL AND INTERNATIONAL QUALITY SCHEMES IN ROMANIA'S 8 DEVELOPMENT REGIONS - Alexandra Gabriela ȘOMÎCU; Marius VLADU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Romania is organized with all the 41 counties into 8 development regions. Some regions have an important representation for quality schemes and products that enrich the cultural and gastronomic heritage of the area. Among the 4,857 certified products at national level, the highest share belongs to mountain products, an aspect which consolidates the national and not necessarily international representativeness. The purpose of the paper is to analyse the status of agri-food products with national recognition and products with international recognition regarding the attestation of quality schemes. The Pearson correlation coefficient and the linear and polynomial regression functions (2nd, 3rd and 4th degree) were used to analyze the relationship between the number of certified products and the number agricultural holdings. The data are collected from national and European registers (e-Ambrosia). For the certified products, the data were extracted for the period 2005-2023, and regarding agricultural holdings, 2002-2020 was analyzed. The results pointed out that there is no direct relationship between agricultural holdings and the number of certified products and that the center and northwest regions are the ones that best represent Romania in terms of agro-food products with gastronomic value and certified quality.